HUBUNGAN DAYA TAHAN KEKUATAN OTOT TUNGKAI DENGAN KECEPATAN RENANG GAYA DADA 100 METER MAHASISWA PENDIDIKAN OLAHRAGA FKIP UNIVERSITAS RIAU - Saripin, Ramadi, Yuherdi, Rafles (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2014)
Problem in the research was started from observation the author encountered in the field that many students have not been able to do 100 metre breaststroke swimming well. It could be seen when students did not finish 100 metre breaststroke swimming. The purpose of this research was to know the legs muscle strength and endurance with a speed of 100 metre breaststroke swimming of the students from Sports Education Riau University. This type of research was correlational. The population in this research was 53 students from Sports Education. Purposive sampling was used to get sample as many as 30 students. To get the data, it was used legs muscle strength and endurance and speed of 100 metre breaststroke swimming. The data were analyzed with correlation simple product moment. Based on the analysis of data, it was found that there was a significant relationship between legs muscle strength and endurance and speed of 100 metre breaststroke swimming of the student form Sports Education Riau University, in which r.count (0,455) > r. table (0,361) on α (0,05).